ANALISIS PENGARUH BAURAN PEMASARAN TERHADAP PENGAMBILAN KEPUTUSAN MENABUNG BRITAMA PADA PT BANK RAKYAT INDONESIA (PERSERO), Tbk CABANG PEMBANTU PURI ANJASMORO SEMARANG - Kinanda Nor Cahya Ningtias; Embun Duriany Soemarso (KEUNIS, 2019)
This study aims to determine the significance of marketing mix variables consisting of product, price, promotion, place, people, processe, and physical evidence of BritAma saving decision making at PT Bank Rakyat Indonesia (Persero), Branch of Puri Anjasmoro Semarang. This study uses primary data from the distribution of questionnaires and secondary data from book literature and research journals. The population of this research is all the savings customers of BritAma PT Bank Rakyat Indonesia (Persero), Tbk Branch of Puri Anjasmoro Semarng. Sampling technique in this research is purposive sampling and accidental sampling. Data analysis method in this research is Multiple Linear Regression Analysis Model. Besides, data quality test in this research is done by using validity test and reliability test, and classical assumption test in the form of normality test, heteroskedasticity test, and multicolonierity test. In this study used data analysis techniques in the form of F test, t test, and coefficient of determination (R2). Based on the results of the analysis and discussion shows that the product, price, promotion, place, person, process, and physical evidence simultaneously significantly influence the decision of saving BritAma at PT Bank Rakyat Indonesia (Persero), Tbk Branch of Puri Anjasmoro Semarang. While partially there are only four variables that have a significant effect on Britama saving decision making is the product, promotion, place, and process. For the other three variables are price, people, and physical evidence have no significant effect on the decision of saving BritAma at PT Bank Rakyat Indonesia (Persero), Tbk Branch of Puri Anjasmoro Semarang.